2019
DOI: 10.1007/s12639-019-01089-4
|View full text |Cite
|
Sign up to set email alerts
|

Ellucidating the incidence and the prevalence of Schistosomiasis spp infection in riparian communities of the Bui dam

Abstract: The flow rate of rivers are affected when modifications are made for the benefit of mankind. Some manmade alterations carried out include dam construction. The aim of this study was to investigate the health impact of the Bui dam with respect to the prevalence and awareness level of schistosomiasis in a typical damming environment. The study was conducted in 4 riparian communities within the dam catchment area. A cross-sectional study design was employed to interview 350 individuals. Urine and stool samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Both S. haematobium and S. mansoni are prevalent in in Ghana [ 214 , 215 , 277 ]. A recent longitudinal study involving 2623 participants including pre-school aged children (pre-SAC), SAC and adults in Ghana recorded an overall prevalence of 44.2% for S. mansoni and 11.9% for S. haematobium , with SAC recording the highest S. haematobium prevalence [ 215 ].…”
Section: A Brief History Of Schistosomiasis In Africamentioning
confidence: 99%
“…Both S. haematobium and S. mansoni are prevalent in in Ghana [ 214 , 215 , 277 ]. A recent longitudinal study involving 2623 participants including pre-school aged children (pre-SAC), SAC and adults in Ghana recorded an overall prevalence of 44.2% for S. mansoni and 11.9% for S. haematobium , with SAC recording the highest S. haematobium prevalence [ 215 ].…”
Section: A Brief History Of Schistosomiasis In Africamentioning
confidence: 99%
“…Inhabitants living close to water bodies have been reported to maintain significantly elevated relative risks for helminth infections and might also be a reason for the burden of helminths observed in the Banda District of the Bono Region, where contact with stagnant water bodies is an important part of daily life, especially for children who are continuously exposed to contaminated soil and water and often lack the awareness of good personal hygiene. Gyasi et al 26 investigated the incidence and prevalence of Schistosoma haematobium infection in riparian communities of the Bui Dam. The study revealed that S. haematobium was more prevalent among inhabitants living closer to the Bui Dam, with children <14 y of age being the worst affected.…”
Section: Discussionmentioning
confidence: 99%
“…The antischistosomal drug is only effective in treating mature infections and does not prevent reinfection (Pica-Mattoccia & Cioli, 2004; Sokolow et al, 2017). As such, the disease continually persists, expands, and intensifies, particularly in regions where water resources have been developed, such as large dams and irrigation systems (Gyasi et al, 2019; Steinmann et al, 2006). It was therefore recommended that mass chemotherapy should be complemented with additional efforts, such as sustainable vector control that is adapted to the local environment (Sokolow et al, 2016).…”
Section: Introductionmentioning
confidence: 99%